2
$\begingroup$

For $f,g \in V =\mathbb{R}[x]_2$, we have the bilinear form \begin{eqnarray*} \phi : &V \times V &\rightarrow \mathbb{R} \\ &(f,g) &\mapsto \int_{-1}^1 xf(x)g(x)dx. \end{eqnarray*} I showed that it is degenerate by observing that ker$(\phi_L) = \left\{a_0\left(1 - \frac{5}{3}x^2\right) \in V \mid a_0 \in \mathbb{R}\right\} \neq \{0\}$. (Maybe this is already where it goes wrong.) I am now to give a basis of $V$ for which the matrix associated to $\phi$ is diagonal. Now while I do have a theorem that guarantees the existence of such a basis, a method to construct such a basis eludes me. $$ H = \left( \begin{array}{rrr} 0 & 0 & 0 \\ 0 & 0 & 0 \\ 0 & 0 & 0 \\ \end{array} \right) $$

$\endgroup$
  • $\begingroup$ well, if you can type in the matrix $H$ using the basis $(1,x,x^2),$ so 3 by 3, I can show you quickly how to change; that is, given symmetric $H$ with rational entries, I can show you how to solve $P^T HP = D$ and $Q^T D Q = H$ with $Q = P^{-1},$ entries of $P$ rational, and $\det P = \pm 1$ $\endgroup$ – Will Jagy Apr 13 '18 at 23:27
  • $\begingroup$ I typed in a matrix $H$ with all entries $0,$ all you need to do is correct the entries to the actual inner products, a symmetric matrix. Since you are beginning with the inner product (rather than a polynomial quadratic form), this construction is called the Gram matrix. $\endgroup$ – Will Jagy Apr 13 '18 at 23:32
  • $\begingroup$ well, if you do edit in the corrections, leave a comment to me here beginning with an "at" sign and and least the first three letters of Will. The next time I look at my main page, there will be a little red flag showing that I have a comment reply and giving a link back here to your comment. $\endgroup$ – Will Jagy Apr 13 '18 at 23:43
  • $\begingroup$ Good, Please find $(1,1)$ and $(1,x) = (x,1)$ and $(1,x^2)= (x^2,1)$ and $(x,x)$ and $(x,x^2)= (x^2,x)$ and $(x^2,x^2)$ and edit those numbers into the matrix in the correct places $\endgroup$ – Will Jagy Apr 13 '18 at 23:51
  • $\begingroup$ Thank you very much @WillJagy! I only now see that I can write the matrix associtated to $\phi$ (in some basis $B = (v_1, v_2, v_3)$) as $[\phi(v_j,v_i)]_{i,j}$. (I figure you guessed I knew that already...) For the basis $B = (1,x,x^2)$ I get $H = $\begin{bmatrix} 0 & 2/3 & 0 \\ 2/3 & 0 & 2/5 \\ 0 & 2/5 & 0\end{bmatrix}. To change the basis, I have found a theorem that seems to suggest something along the lines of what you said, so I think I'll get there now myself. Many thanks! $\endgroup$ – Jos van Nieuwman Apr 13 '18 at 23:52
1
$\begingroup$

Multiplying the columns of $P$ by $( 1,-2, -5)$ suggests the basis $$ \{ \; 1+x, \; \; 1-x, \; \; 3 - 5 x^2 \; \} $$

$$ P^T H P = D $$ $$\left( \begin{array}{rrr} 1 & 1 & 0 \\ - \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & 0 \\ - \frac{ 3 }{ 5 } & 0 & 1 \\ \end{array} \right) \left( \begin{array}{rrr} 0 & \frac{ 2 }{ 3 } & 0 \\ \frac{ 2 }{ 3 } & 0 & \frac{ 2 }{ 5 } \\ 0 & \frac{ 2 }{ 5 } & 0 \\ \end{array} \right) \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & - \frac{ 3 }{ 5 } \\ 1 & \frac{ 1 }{ 2 } & 0 \\ 0 & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} \frac{ 4 }{ 3 } & 0 & 0 \\ 0 & - \frac{ 1 }{ 3 } & 0 \\ 0 & 0 & 0 \\ \end{array} \right) $$ $$ Q^T D Q = H $$ $$ \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & - \frac{ 3 }{ 5 } \\ 1 & \frac{ 1 }{ 2 } & 0 \\ 0 & 0 & 1 \\ \end{array} \right) \left( \begin{array}{rrr} \frac{ 4 }{ 3 } & 0 & 0 \\ 0 & - \frac{ 1 }{ 3 } & 0 \\ 0 & 0 & 0 \\ \end{array} \right) \left( \begin{array}{rrr} 1 & 1 & 0 \\ - \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & 0 \\ - \frac{ 3 }{ 5 } & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} 0 & \frac{ 2 }{ 3 } & 0 \\ \frac{ 2 }{ 3 } & 0 & \frac{ 2 }{ 5 } \\ 0 & \frac{ 2 }{ 5 } & 0 \\ \end{array} \right) $$

ORIGINAL: I multiply your matrix by $15/2$ to get integers. To apply to your specific matrix, multiply both $H$ and $D$ by $2/15.$

$$ P^T H P = D $$ $$\left( \begin{array}{rrr} 1 & 1 & 0 \\ - \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & 0 \\ - \frac{ 3 }{ 5 } & 0 & 1 \\ \end{array} \right) \left( \begin{array}{rrr} 0 & 5 & 0 \\ 5 & 0 & 3 \\ 0 & 3 & 0 \\ \end{array} \right) \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & - \frac{ 3 }{ 5 } \\ 1 & \frac{ 1 }{ 2 } & 0 \\ 0 & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} 10 & 0 & 0 \\ 0 & - \frac{ 5 }{ 2 } & 0 \\ 0 & 0 & 0 \\ \end{array} \right) $$ $$ Q^T D Q = H $$ $$\left( \begin{array}{rrr} \frac{ 1 }{ 2 } & - 1 & 0 \\ \frac{ 1 }{ 2 } & 1 & 0 \\ \frac{ 3 }{ 10 } & - \frac{ 3 }{ 5 } & 1 \\ \end{array} \right) \left( \begin{array}{rrr} 10 & 0 & 0 \\ 0 & - \frac{ 5 }{ 2 } & 0 \\ 0 & 0 & 0 \\ \end{array} \right) \left( \begin{array}{rrr} \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & \frac{ 3 }{ 10 } \\ - 1 & 1 & - \frac{ 3 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} 0 & 5 & 0 \\ 5 & 0 & 3 \\ 0 & 3 & 0 \\ \end{array} \right) $$

Algorithm discussed at http://math.stackexchange.com/questions/1388421/reference-for-linear-algebra-books-that-teach-reverse-hermite-method-for-symmetr
$$ H = \left( \begin{array}{rrr} 0 & 5 & 0 \\ 5 & 0 & 3 \\ 0 & 3 & 0 \\ \end{array} \right) $$ $$ D_0 = H $$

$$ E_j^T D_{j-1} E_j = D_j $$ $$ P_{j-1} E_j = P_j $$ $$ E_j^{-1} Q_{j-1} = Q_j $$ $$ P_j Q_j = Q_j P_j = I $$ $$ P_j^T H P_j = D_j $$ $$ Q_j^T D_j Q_j = H $$

$$ H = \left( \begin{array}{rrr} 0 & 5 & 0 \\ 5 & 0 & 3 \\ 0 & 3 & 0 \\ \end{array} \right) $$

==============================================

$$ E_{1} = \left( \begin{array}{rrr} 1 & 0 & 0 \\ 1 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) $$ $$ P_{1} = \left( \begin{array}{rrr} 1 & 0 & 0 \\ 1 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; Q_{1} = \left( \begin{array}{rrr} 1 & 0 & 0 \\ - 1 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; D_{1} = \left( \begin{array}{rrr} 10 & 5 & 3 \\ 5 & 0 & 3 \\ 3 & 3 & 0 \\ \end{array} \right) $$

==============================================

$$ E_{2} = \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) $$ $$ P_{2} = \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & 0 \\ 1 & \frac{ 1 }{ 2 } & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; Q_{2} = \left( \begin{array}{rrr} \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & 0 \\ - 1 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; D_{2} = \left( \begin{array}{rrr} 10 & 0 & 3 \\ 0 & - \frac{ 5 }{ 2 } & \frac{ 3 }{ 2 } \\ 3 & \frac{ 3 }{ 2 } & 0 \\ \end{array} \right) $$

==============================================

$$ E_{3} = \left( \begin{array}{rrr} 1 & 0 & - \frac{ 3 }{ 10 } \\ 0 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) $$ $$ P_{3} = \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & - \frac{ 3 }{ 10 } \\ 1 & \frac{ 1 }{ 2 } & - \frac{ 3 }{ 10 } \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; Q_{3} = \left( \begin{array}{rrr} \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & \frac{ 3 }{ 10 } \\ - 1 & 1 & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; D_{3} = \left( \begin{array}{rrr} 10 & 0 & 0 \\ 0 & - \frac{ 5 }{ 2 } & \frac{ 3 }{ 2 } \\ 0 & \frac{ 3 }{ 2 } & - \frac{ 9 }{ 10 } \\ \end{array} \right) $$

==============================================

$$ E_{4} = \left( \begin{array}{rrr} 1 & 0 & 0 \\ 0 & 1 & \frac{ 3 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) $$ $$ P_{4} = \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & - \frac{ 3 }{ 5 } \\ 1 & \frac{ 1 }{ 2 } & 0 \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; Q_{4} = \left( \begin{array}{rrr} \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & \frac{ 3 }{ 10 } \\ - 1 & 1 & - \frac{ 3 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) , \; \; \; D_{4} = \left( \begin{array}{rrr} 10 & 0 & 0 \\ 0 & - \frac{ 5 }{ 2 } & 0 \\ 0 & 0 & 0 \\ \end{array} \right) $$

==============================================

$$ P^T H P = D $$ $$\left( \begin{array}{rrr} 1 & 1 & 0 \\ - \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & 0 \\ - \frac{ 3 }{ 5 } & 0 & 1 \\ \end{array} \right) \left( \begin{array}{rrr} 0 & 5 & 0 \\ 5 & 0 & 3 \\ 0 & 3 & 0 \\ \end{array} \right) \left( \begin{array}{rrr} 1 & - \frac{ 1 }{ 2 } & - \frac{ 3 }{ 5 } \\ 1 & \frac{ 1 }{ 2 } & 0 \\ 0 & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} 10 & 0 & 0 \\ 0 & - \frac{ 5 }{ 2 } & 0 \\ 0 & 0 & 0 \\ \end{array} \right) $$ $$ Q^T D Q = H $$ $$\left( \begin{array}{rrr} \frac{ 1 }{ 2 } & - 1 & 0 \\ \frac{ 1 }{ 2 } & 1 & 0 \\ \frac{ 3 }{ 10 } & - \frac{ 3 }{ 5 } & 1 \\ \end{array} \right) \left( \begin{array}{rrr} 10 & 0 & 0 \\ 0 & - \frac{ 5 }{ 2 } & 0 \\ 0 & 0 & 0 \\ \end{array} \right) \left( \begin{array}{rrr} \frac{ 1 }{ 2 } & \frac{ 1 }{ 2 } & \frac{ 3 }{ 10 } \\ - 1 & 1 & - \frac{ 3 }{ 5 } \\ 0 & 0 & 1 \\ \end{array} \right) = \left( \begin{array}{rrr} 0 & 5 & 0 \\ 5 & 0 & 3 \\ 0 & 3 & 0 \\ \end{array} \right) $$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.